Pengaruh Sustainability Report terhadap Kinerja Keuangan Perusahaan Perbankan yang Terdaftar di Bursa Efek Indonesia Tahun 2021–2025 - Rachmaudina Digna Fadhilah; Elsa Imelda (Ikatan Da'i Indonesia, 2026)
This study aims to analyze the effect of Sustainability Report disclosure on the financial performance of banking sector companies listed on the Indonesia Stock Exchange (IDX) during the 2021–2025 period. The population consists of banking sector companies listed on the IDX. Using the purposive sampling method, a sample of 27 companies was obtained, resulting in 116 observations after the removal of outlier data. The independent variables are Sustainability Report disclosures, consisting of the economic dimension (Economic Disclosure Index/EcDI), the environmental dimension (Environmental Disclosure Index/EnDI), and the social dimension (Social Disclosure Index/SoDI). The dependent variable is financial performance, proxied by the profitability ratio Return on Assets (ROA). In addition, firm size (SIZE) and leverage (LEV) are used as control variables. This study employs a quantitative approach using panel data regression analysis. Based on the Chow Test, Hausman Test, and Lagrange Multiplier Test conducted using EViews 12, the Random Effect Model (REM) was selected as the most appropriate model. The results show that EcDI disclosure has a negative and significant effect on ROA, while firm size (SIZE) has a positive and significant effect on ROA. Meanwhile, EnDI, SoDI, and leverage (LEV) have no significant effect on ROA.